Refining and Analysis of Cooking Oil (Waste Cooking Oil) Using Rice with The Batch Method - Nila Tanyela Berghuis; Ana Farida; Sayyidah Afifa; Mazaya Aurora; Brikita Eusebes; Salsa Putri (Helium: Journal of Science and Applied Chemistry, 2022)
The regular use of waste cooking oil, which has a high level of free fatty acids and carbonyl and peroxide compounds, is the background of this study, which is harmful to one's health. Using it indefinitely will harm health, including cancer, heart disease, and possibly death. We, therefore, performed research on the purification and analysis of waste cooking oil using white rice and aking rice with the batch method to detect the free fatty acid levels before and after purification and to establish the effectiveness of white rice and aking rice. Determine the utilized cooking oil's quality following filtration using adsorbent. The findings demonstrated that white rice was more effective than aking rice at reducing fatty acid levels, as shown by the acquisition of FFA levels using white rice of 0.3141% in the merchant oil sample and 0.2410% in the home oil sample. In comparison, purification with the aking rice adsorbent is 0.3474% in the merchant oil sample and 0.1374% in the home oil sample.